Serum Adiponectin Variation And Its Relationships With Certain Markers Of Cardiovascular And Metabolic Risk In Type 2 Diabetes (International Journal of Physiology, 2024)
Introduction : adiponectin seems to participate in the pathophysiology of comorbidities associated with obesity such as type 2 diabetes. Thus, we propose to determine the correlation of serum adiponectin to clinico-biological parameters in type 2 diabetes.Methodology : this is a case-control study with a bio-anthropometric and a biochemical examination in all participants. The arterial stiffness and the endothelial dysfunction were evaluated. Serum adiponectin and nitric oxide levels were measured by the ELISA sandwich test.Results : serum adiponectin was significantly lower in type 2 diabetic subjects (p